Challenges and opportunities in developing novel drugs for TB. (September 2011) - Kaneko, Takushi; Cooper, Christopher; Mdluli, Khisimuzi
Mycobacterium tuberculosis is a difficult pathogen to combat and the first-line drugs currently in use are 40–60 years old. The need for new TB drugs is urgent, but the time to identify, develop and ultimately advance new drug regimens onto the market has been excruciatingly slow. On the other hand, the drugs currently in clinical development, and the recent gains in knowledge of the pathogen and the disease itself give us hope for finding new drug targets and new drug leads. In this article we highlight the unique biology of the pathogen and several possible ways to identify new TB chemical leads. The Global Alliance for TB Drug Development (TB Alliance) is a not-for-profit organization whose mission is to accelerate the discovery and development of new TB drugs. The organization carries out research and development in collaboration with many academic laboratories and pharmaceutical companies around the world. In this perspective we will focus on the early discovery phases of drug development and try to provide snapshots of both the current status and future prospects.